Effects of cord clamping time on hemoglobin levels in neonates - Kartini, Farida; Hakimi, Moh.; Guterres, Ana Claudia da Costa (Alma Ata University Press, 2025)
Background: Delaying cord clamping can increase the baby’s hemoglobin levels. Most of these studies compared delayed cord clamping with a baby’s hemoglobin levels at a few months of birth and not with hemoglobin levels in newborns. After the baby is born, the baby’s circulatory system is no longer related to the mother’s circulatory system. In the fetus, nutrients are obtained directly from the mother’s blood circulation through diffusion, so all the substances from the diffusion may enter the fetus’s body. Thus, if the baby’s hemoglobin level is not measured immediately after birth, the results will likely differ. This study checked the baby’s hemoglobin levels within 48 hours after birth.Objectives: This study aims to determine the relationship between the timing of cord clamping and newborn hemoglobin levels. Methods: This study is correlational research. The study population consists of medical records of maternity mothers and newborns from the Midwife’s Independent Practice in the Bantul area. There were 118 records total, with 84 meeting the inclusion criteria. Data analysis employs Spearman’s Rank correlation. Results: Of the 84 newborns, one had a hemoglobin level of 12.3 g/dL, indicating anemia. In this baby, cord clamping was performed 11 minutes after birth or after the umbilical cord stopped pulsating. The rest have levels above 20 g/dl, ranging from 20.3 to 25.9 g/dl, which includes 65 babies (77.4%). When referencing normal newborn hemoglobin levels, the largest range appears in the polycythemia category. The Spearman Rank test showed a p-value of 0.271. Conclusions: The timing of cord clamping was unrelated to newborn hemoglobin levels.